The impact of airborne particulate matter on pediatric hospital admissions for pneumonia among children in Jinan, China: A case-crossover study. (3rd June 2017) - Lv, Chenguang; Wang, Xianfeng; Pang, Na; Wang, Lanzhong; Wang, Yuping; Xu, Tengfei; Zhang, Yu; Zhou, Tianran; Li, Wei
ABSTRACT: This study aims to examine the effect of short-term changes in the concentration of particulate matter of diameter ≤2.5 µm (PM2.5 ) and ≤10 µm (PM10 ) on pediatric hospital admissions for pneumonia in Jinan, China. It explores confoundings factors of weather, season, and chemical pollutants. Information on pediatric hospital admissions for pneumonia in 2014 was extracted from the database of Jinan Qilu Hospital. The relative risk of pediatric hospital admissions for pneumonia was assessed using a case-crossover approach, controlling weather variables, day of the week, and seasonality. The single-pollutant model demonstrated that increased risk of pediatric hospital admissions for pneumonia was significantly associated with elevated PM2.5 concentrations the day before hospital admission and elevated PM10 concentrations 2 days before hospital admission. An increment of 10 μg/m 3 in PM2.5 and PM10 was correlated with a 6% (95% CI 1.02–-1.10) and 4% (95% CI 1.00–1.08) rise in number of admissions for pneumonia, respectively. In two pollutant models, PM2.5 and PM10 remained significant after inclusion of sulfur dioxide or nitrogen dioxide but not carbon monoxide. This study demonstrated that short-term exposure to atmospheric particulate matter (PM2.5 /PM10 ) may be an important determinant of pediatric hospital admissions for pneumonia in Jinan, China. Implications : This study demonstrated that short-term exposure to atmospheric particulate matter (PM2.5 /PM10 ) may be an important determinant of pediatric hospital admissions for pneumonia in Jinan, China, and suggested the relevance of pollutant exposure levels and their effects. As a specific group, children are sensitive to airborne particulate matter. This study estimated the short-term effects attribute to other air pollutants to provide references for relevant studies.